Comparative Study of Municipal Solid Waste Fuel and Refuse Derived Fuel in the Gasification Process Using Multi Stage Downdraft Gasifier - Sigit Mujiarto; Bambang Sudarmanta; Hamzah Fansuri; Arif Rahman Saleh (Universitas Muhammadiyah Magelang, 2021)
Municipal solid waste (MSW) is a type of general waste that includes households, traditional markets, commercial areas, and the rest from public facilities, schools, offices, roads, and so on. Refuse Derived Fuel (RDF) is obtained from the remnants of MSW which cannot be used anymore, which is flammable waste and is separated from parts that are difficult to burn through the process of chopping, sifting, and air classification. RDF has potential as an alternative energy source. In this study, RDF fuel was compared with MSW fuel both by proximate and calorific value, then the gasification process was carried out using a multi-stage downdraft gasifier to see gasification performance indicators such as syngas composition, LHV, cold gas efficiency, and tar concentration. The results showed that the gasification performance indicator for MSW biomass resulted in the syngas composition of CO = 19.08% v, H2 = 10.89% v, and CH4 = 1.54% v. The calorific value (Low Heating Value, LHV ) of syngas is 4,137 kJ/kg, cold gas efficiency is 70.14%, and tar content is 57.29 mg/Nm3. Meanwhile, RDF obtained the composition of CO gas: 18.68% v, H2: 9.5446% v, and CH4: 0% v. The maximum LHV syngas is 3365.08 kJ/kg, cold gas efficiency is 57.19 % and the smallest tar content is 80.24 mg/Nm3. When compared to RDF, MSW produces a better gasification performance indicator. However, RDF can still be used as an alternative energy source using the gasification process. The results of this study can be used to optimize the further RDF gasification process.